WhatsApp Bot in Hadith Search Using The Full-text Indexes Method and Text Mining: Bot WhatsApp dalam Pencarian Hadits Menggunakan Metode Indeks Teks Lengkap dan Penambangan Teks - Muchlis (Universitas Singaperbangsa Karawang, 2021)
The WhatsApp application is now one of the most widely used media by all circles, from school children, professionals and even religious teachers use it. The ability of WhatsApp can be used by many fields in social life, such as phone calls, chats, groups and others. Because people are now accustomed to using WhatsApp, it can also be used to convey knowledge such as about hadith searches which are usually done by people who need information or knowledge about certain hadiths. This WhatsApp application will display the search results made by the searcher through the message sent. The message sent to this special number sends a word or several words in the message which will be processed by the system via the Restful API to the database. This system provides a random response to search results by displaying how many hadiths are related to the search.